Synchronous body-to-body coupling to reflect collaborative and competitive engagement in verbal communication - Grover, Ayush (Nanyang Technological University, 2024)
The influence of interpersonal body coordination on interactions in verbal communication remains underexplored. This project investigates how competitive and collaborative engagement between talkers affect their Body-to-Body Coupling (BtBC). We propose a novel approach using computer vision-based Motion Energy Analysis (MEA) software to quantify BtBC between communication partners during collaborative and competitive sessions. By analysing both nonverbal communication cues and BtBC patterns, we aim to decode the mode of engagement between participants. This project explores the design and integration of this methodology for potential deployment in settings such as education (in-person and online learning) and healthcare (therapy sessions).